Cowboys, poets, professor... - Antonomasia in Sports Discourse - Grgić, Ana, kroatistica (Array, 2013)
Antonomasia is defined both as a trope that substitutes proper name by an appellative, epithet or periphrasis and as a trope that substitutes certain traits by a proper name. The second type is usually called Vossian antonomasia (named after Gerardus Johannis Vossius, 17th century Dutch rhetorician). Defined in the broader sense, antonomasia can be regarded as a trope that relies on the processes of appellativization and deappellativization, both common in everyday language. News style (or journalistic style) depends on the frequent use of tropes, especially metaphors and metonymies. Previous research of Croatian newspaper headlines (Ivas 2004) showed that antonomasia is also a very frequent trope in headlines of the journal articles. This research wanted to further explore types of antonomasia in the sports news sub-style. Besides the types of antonomasia (metonymic or metaphoric), we also analyzed the frequency of the proper name substitution both in the headlines and in the full news text. The corpus consisted of three groups of sports news: sports news articles in the daily newspapers ; articles in the specialized sports newspapers and magazines ; and the central sports news in the daily news program of three Croatian national networks (HRT, Nova TV and RTL). The analysis confirmed that antonomasias are mostly used in the headlines and that journalists tend to use antonomasia more frequently in written articles than in the television news. Sports antonomasias mostly substitute names of athletes, sports clubs and national selections, but also sports fans, sports arenas and the hosting cities (or lands) of sports events. Our research confirmed the dominance of metonymic origin of sports antonomasia with specific Croatian homophonic relations in periphrastic antonomasias.